2009
DOI: 10.1021/ef9003329
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Capture of CO2from Simulated Flue Gas by Formation of TBAB or TBAF Semiclathrate Hydrates

Abstract: Capturing CO 2 by forming hydrate is an attractive technology for reducing the greenhouse effect. The most primary challenges are high energy consumption, low hydrate formation rate, and separation efficiency. This work presents efficient capture of CO 2 from simulated flue gas (CO 2 (16.60 mol %)/N 2 binary mixtures) by formation of semiclathrate hydrates at 4.5 and 7.1 °C and feed pressures ranging from 2.19 to 7.31 MPa. The effect of 0.293 mol % tetra-n-butyl ammonium bromide (TBAB) and tetra-n-butyl ammoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
131
4
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(142 citation statements)
references
References 20 publications
4
131
4
1
Order By: Relevance
“…As seen in the figure, the CO 2 recovery is higher in the new apparatus compared to the laboratory scale apparatus and also higher than experiments conducted with TBAB and TBAF Li et al, 2009). Fan et al (2009) reported a final gas consumption (calculated based on pressure drop data) of 0.14-0.32 moles for experimental pressures between 3.4 and 7.3 MPa in the presence of TBAB and 0.063-0.191 moles for experimental pressures between 2.2 and 6.8 MPa in the presence of TBAF. Taking into account the amount of water report 600 cm 3 of liquid contents) taken for experiments, gas consumption on a water free basis is 0.004-0.010 mol of gas per mol of water for experimental pressures between 3.4 and 7.3 MPa for TBAB containing system and 0.002-0.006 mol of gas per mol of water for experimental pressures between 2.2 and 6.8 MPa for TBAF containing system.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…As seen in the figure, the CO 2 recovery is higher in the new apparatus compared to the laboratory scale apparatus and also higher than experiments conducted with TBAB and TBAF Li et al, 2009). Fan et al (2009) reported a final gas consumption (calculated based on pressure drop data) of 0.14-0.32 moles for experimental pressures between 3.4 and 7.3 MPa in the presence of TBAB and 0.063-0.191 moles for experimental pressures between 2.2 and 6.8 MPa in the presence of TBAF. Taking into account the amount of water report 600 cm 3 of liquid contents) taken for experiments, gas consumption on a water free basis is 0.004-0.010 mol of gas per mol of water for experimental pressures between 3.4 and 7.3 MPa for TBAB containing system and 0.002-0.006 mol of gas per mol of water for experimental pressures between 2.2 and 6.8 MPa for TBAF containing system.…”
Section: Resultsmentioning
confidence: 72%
“…The normalized rate of gas supply calculated by taking into account of the volume of water (Eq. (3)) for the experiments conducted in the presence of 1.0 mol% THF in the lab-scale apparatus and the new large scale apparatus (this work) and data available in Fan et al (2009).…”
Section: Resultsmentioning
confidence: 99%
“…In other words, SCHs are capable of selectively incorporating small gas guest molecules within the small cavities of the SCHs. Unlike ordinary hydrates having well defined structures (Structure I, Structure II, and Structure H), SCHs have diverse structures and have hydrogen-bonding interaction between guests and hosts molecules, which is much stronger than the van der Waals force in ordinary hydrates 5 SCHs have drawn increasingly more interest from researchers for their potential applications in hydrogen storage 8 , carbon dioxide storage 9 , and gas separation [10][11][12][13][14] . The thermodynamic data of SCHs are limited, and the majority of them are for TBAB 8,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the satisfactory separation efficiency of current CO 2 capture methods, a challenge remains as to how to reduce the cost and achieve high regenerability [3,4]. One of the most promising attempts for addressing this challenge is CO 2 hydrate formation [5][6][7][8][9][10][11][12]. CO 2 hydrate is one of gas hydrates that are inclusion compounds with cages formed by the hydrogen-bonded water molecules and guest species [13].…”
Section: Introductionmentioning
confidence: 99%